HUBUNGAN KUALITAS PELAYANAN DENGAN KEPUASAN PELANGGAN PADA SALON KENCANTIKAN DI KABUPATEN PASAMAN BARAT - indriyani, Witri - (journal of residu, 2019)
The background of this research relates to the influence of quality of service measured through five dimensional tangible, realibility, emphaty, assurance, responsiviness to the perceived satisfaction of the customers of beauty salons in West Pasaman district. This research aims to know and analyze the quality, satisfaction and relationship of quality service customers felt in using beauty salon services in West Pasaman district. This type of research is quantitative descriptive research. The population in this research is the all-customer beauty salon in West Pasaman Regency with samples of 77 people. Data types use primary data and secondary data. The variables in this study are the satisfaction of the auction, quality of service, measuring scale, testing of data instruments. Stages for analyzing data using the stage method of testing hypotheses by using statistical testing tools. The results showed that the results of the hypotheses that had been done were seen that the resulting T-count value was 6,830 that value was strengthened by a sig of 0.000. The data processing process is done using error rate of 0.05. Results obtained showing a sig value of 0.000 is below the error rate of 0.05 then it can be concluded that the quality of service is positive and significant to customer satisfaction in using the services of beauty salons in City of Simpang Empat West Pasaman Regency. According to the results of testing coefficient of determination acquired value of R2 coefficient of 0709. The results showed that the quality of service is able to provide a variation of contributions in influencing the satisfaction of consumers who use beauty salons in the city of Simpang four Pasaman Bara 70.90% while the remaining 29.10% more Described by other variables that are not used in the current research model.